2017
DOI: 10.1371/journal.pone.0186777
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to inhaled therapies of COPD patients from seven Latin American countries: The LASSYC study

Abstract: BackgroundThis study assessed the adherence profiles to inhaled therapies and the agreement between two patient self-report adherence methods in stable COPD lpatients from seven Latin American countries.MethodsThis observational, cross-sectional, multinational, multicenter study involved 795 COPD patients (post-bronchodilator forced expiratory volume in 1 second/forced vital capacity [FEV1/FVC] <0.70). Adherence to inhaled therapy was assessed using the specific Test of Adherence to Inhalers (10-item TAI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 24 publications
9
39
1
3
Order By: Relevance
“…The Latin American Study of 24-hour Symptoms in Chronic Obstructive Pulmonary Disease (LASSYC) was a prospective observational, multicenter, multinational, cross-sectional, non-interventional study in stable COPD patients from seven Latin American countries: Argentina, Chile, Colombia, Costa Rica, Guatemala, Mexico, and Uruguay. 11 , 12 The study has been registered at ClinicalTrials.gov (identifier: NCT02789540). Here, we analyzed prescribed medication use and adherence to different inhaled therapies in this patient population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Latin American Study of 24-hour Symptoms in Chronic Obstructive Pulmonary Disease (LASSYC) was a prospective observational, multicenter, multinational, cross-sectional, non-interventional study in stable COPD patients from seven Latin American countries: Argentina, Chile, Colombia, Costa Rica, Guatemala, Mexico, and Uruguay. 11 , 12 The study has been registered at ClinicalTrials.gov (identifier: NCT02789540). Here, we analyzed prescribed medication use and adherence to different inhaled therapies in this patient population.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, outpatients ≥40 years of age with a diagnosis of COPD for at least 1 year, at least one spirometry value with a COPD diagnosis using the post-bronchodilator FEV 1 /FVC <0.70 criterion in the previous 12 months, current or ex-smokers (≥10 pack-years), and stable disease (without treatment for an exacerbation or changes in current treatment in the previous 2 months) were included in the study. 11 Patients with a diagnosis of sleep apnea or any other chronic respiratory disease, or any acute or chronic condition that would limit their ability to participate in the study were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The Latin American Study of 24-hour SYmptoms in Chronic Obstructive Pulmonary Disease (LASSYC) was an observational, multicentre, multinational, cross-sectional, non-interventional study (Clinical Trial Registration: NCT02789540), the objective of which was to describe prevalence, severity and inter-relationship of early morning, day and night-time symptoms with COPD severity, exacerbations and patient reported outcomes (PROs) in patients with stable COPD from seven Latin American countries (Argentina, Chile, Colombia, Costa Rica, Guatemala, Mexico and Uruguay) [7]. The study was approved by the ethics committees for each site and all patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Poor medication adherence is a particular concern in COPD, because it has been associated with higher rates of exacerbations, 11,12 hospitalizations, [12][13][14] mortality, 11 and increased health care costs. [12][13][14] Real-world studies worldwide have reported suboptimal adherence to COPD maintenance therapy 12,15,16 ; this may be attributed to multiple factors, including use of multiple inhalers, 17 inhaler type, 18 multiple daily doses, 14 cost burden, 19 presence of depression, 20 and patient preferences and beliefs. 19 Because previous real-world studies of adherence to COPD medications have generally used data from claims databases or patient questionnaires, 12,[14][15][16] limited data are available on assessment of medication adherence and symptom burden in COPD in a community pharmacy setting, particularly in U.S. populations.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Real-world studies worldwide have reported suboptimal adherence to COPD maintenance therapy 12,15,16 ; this may be attributed to multiple factors, including use of multiple inhalers, 17 inhaler type, 18 multiple daily doses, 14 cost burden, 19 presence of depression, 20 and patient preferences and beliefs. 19 Because previous real-world studies of adherence to COPD medications have generally used data from claims databases or patient questionnaires, 12,[14][15][16] limited data are available on assessment of medication adherence and symptom burden in COPD in a community pharmacy setting, particularly in U.S. populations. However, community pharmacists, with their unique role in management of patients with COPD, 21 are well positioned within the health care team to provide insights into patient behavior that cannot be obtained from claims data alone.…”
Section: Introductionmentioning
confidence: 99%